Smallholder Farmers’ Decision and Level of Participation in the Potato Market in Uganda - Sebatta, Christopher; Mugisha, Johnny; Katungi, Enid; Kashaaru, Apolo; Kyomugisha, Harriet (Modern Economy, 2014)
Smallholder potato farmers in Uganda face many production and marketing challenges including limited access to markets and low surpluses for sale into the market. This study sought to underscore the factors that influence smallholder farmers’ decision to participate in the potato market and level of participation in such markets. Data were collected from 200 smallholder potato farmers in Kabale and Mbale districts. Descriptive statistics and a two-stage Heckman model were used to analyse the data. Results indicated that proximity to a village market positively and significantly (p ≤ 0.05) influenced decision to participate in the potato market. Results of the second stage of the model indicated that non-farm income earned negatively and significantly (p ≤ 0.01) affected the potato farmer’s level of market participation.
Keywords: Smallholder Farmers, Market Participation, Heckman Model